Impact of Life Events on Happiness through Moderating Role of Belief in Just World among Adults - Sher Bahader; Asghar Ali Shah; Mazhar Iqbal Bhatti, (ASIAN Journal of International Peace & Security (AJIPS), 2022)
This study was designed to investigate how a person’s life events affect his general happiness as well as relationship between life events, belief in just world, and general happiness among adults. Further, age differences, family structure, living style and educational status etc. on all constructs were determined. For this purpose, data N= 200 was taken from different government and non-government university students by using the purposive sampling technique. Pearson Product Moment correlation, Multiple Regression Analysis, Moderation analysis, t-test, were used to analyze the data. The results elaborated that there is a significant positive correlation between positive life events and general happiness as well as significant positive correlation between positive life events and belief in just world while significantly negative relationship of positive life events with negative life events. Negative life events negatively associated with belief in just world as well as general happiness; belief in just world significantly positively associated with general happiness; belief in just world significantly moderate in the relationship between positive life events and general happiness. The research emphasizes the importance of personal attributes in understanding how an individual's belief strengthens happiness in 'troubled' populations.